Knowledge, Social Influences, Perceived Risks and Benefits, and Cultural Values Explain the Public's Decisions Related to Prudent Antibiotic Use. Issue 7 (16th November 2021) - Visschers, Vivianne H. M.; Feck, Vanessa; Herrmann, Anne
Abstract: People should use antibiotics (AB) prudently to mitigate antibiotic resistance (ABR). Previous studies—and, subsequently, interventions—on ABR have focused mainly on improving public awareness and knowledge. We investigated a comprehensive theory‐based explanatory model to understand the public's decision making regarding prudent AB use, based on, among others, the theory of planned behavior. In a cross‐sectional online survey, the psychological determinants of people's decisions about prudent AB use were examined in a sample of 1, 228 Swiss adults. The questionnaire assessed respondents' demand for AB, willingness to adopt measures that prevent the need for AB, perceived risks of ABR, perceived benefits of AB, attitudes and social influences regarding AB, knowledge of AB and ABR, and cultural values. Mokken scale analysis revealed three types of knowledge: knowledge of the functioning of AB, of ABR, and of preventive measures. Structural equation modeling indicated that respondents' demand for AB was mostly predicted by social influences, perceived benefits of AB, and knowledge of AB functioning. Willingness to prevent AB use was mainly related to conservative values, perceived risks of ABR, negative attitudes toward AB, and knowledge of preventive measures. Our study suggests that the provision of information about AB and preventive measures is a first step toward changing people's decisions related to prudent AB use. Future interventions that additionally utilize cultural values to convey important messages and target additional factors, such as social influences, the risks of ABR, and the benefits of cautious AB use, can be more successful in promoting prudent AB use.